2019
DOI: 10.3847/1538-4357/ab3a43
|View full text |Cite
|
Sign up to set email alerts
|

How Galactic Environment Affects the Dynamical State of Molecular Clouds and Their Star Formation Efficiency

Abstract: We investigate how the dynamical state of molecular clouds relates to host galaxy environment, and how this impacts the star formation efficiency in the Milky Way and seven nearby galaxies. We compile measurements of molecular cloud and host galaxy properties and determine mass-weighted mean cloud properties for entire galaxies and distinct subregions within. We find molecular clouds to be in ambient pressure-balanced virial equilibrium, where clouds in gas-rich, molecular-dominated, high-pressure regions are … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
126
4

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 101 publications
(140 citation statements)
references
References 167 publications
10
126
4
Order By: Relevance
“…Based on observations from the PdBI Arcsecond Whirlpool Survey (Pety et al 2013;Schinnerer et al 2013), Hughes et al (2013aHughes et al ( , 2013b and Colombo et al (2014) showed strong variations in GMC properties within the inner ∼4 kpc of M51 and among M51, M33, and the Large Magellanic Cloud (LMC). Similar results were found by subsequent works studying GMCs in various types of galaxies in the local universe (e.g., Donovan Meyer et al 2013;Leroy et al 2015;Rebolledo et al 2015;Utomo et al 2015;Freeman et al 2017;Egusa et al 2018;Hirota et al 2018;Schruba et al 2019).…”
Section: Introductionsupporting
confidence: 90%
See 3 more Smart Citations
“…Based on observations from the PdBI Arcsecond Whirlpool Survey (Pety et al 2013;Schinnerer et al 2013), Hughes et al (2013aHughes et al ( , 2013b and Colombo et al (2014) showed strong variations in GMC properties within the inner ∼4 kpc of M51 and among M51, M33, and the Large Magellanic Cloud (LMC). Similar results were found by subsequent works studying GMCs in various types of galaxies in the local universe (e.g., Donovan Meyer et al 2013;Leroy et al 2015;Rebolledo et al 2015;Utomo et al 2015;Freeman et al 2017;Egusa et al 2018;Hirota et al 2018;Schruba et al 2019).…”
Section: Introductionsupporting
confidence: 90%
“…In this case, a version of dynamical equilibrium is reached-at least in a population-averaged sense-on cloud scales. In a recent observational study, Schruba et al (2019) have shown that GMCs in the Milky Way and seven nearby galaxies indeed appear to achieve this equilibrium state when averaged over the population.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, such a simplistic approach neglects the acceleration due to the molecular phase of the ISM and the stellar disc which is particularly important in low-density environments (e.g. Schruba et al 2019). The consistency between the measured time-scale associated with the atomic clouds and the predicted time-scale for the gravitational collapse of the ISM (the ISM free-fall timescale in Fig.…”
Section: H I Time-scales In Contextmentioning
confidence: 98%